HUBUNGAN PENDIDIKAN MULTIKULTURAL BERBASIS KEARIFAN LOKAL DENGAN SIKAP TOLERANSI SISWA SEKOLAH DASAR - Fadlayani; Nurul Auliya Lukman; Ridhatul Husna; Nurul Hikma (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the relationship between multicultural education based on local wisdom and elementary school students' tolerance attitudes, as well as to identify factors influencing its implementation. The background of this research is the importance of instilling tolerance values from an early age amidst the diversity of cultures, ethnicities, and religions in Indonesia, as well as the ongoing challenges in the implementation of multicultural education in the field. The study employed a quantitative approach with a correlational design. The population and simultaneously the sample were all 25 fifth-grade students of SD Negeri Kassi, taken using total sampling technique. The data collection instrument was a four-point Likert scale questionnaire that had been tested for validity using Pearson Product Moment correlation and for reliability using Cronbach's Alpha coefficient. Data analysis was conducted through the Shapiro-Wilk normality test and the Pearson correlation test. The results showed that there is a significant positive relationship between multicultural education based on local wisdom and students' tolerance attitudes, with a correlation coefficient of r = 0.536 and a significance value of p = 0.006 (p < 0.01), which falls into the moderate relationship category. The implementation of multicultural education based on local wisdom at SD Negeri Kassi was classified as high (83.99%), and students' tolerance attitudes were in the very high category (87.50%). These findings are reinforced by the literature review affirming that local wisdom values—such as mutual cooperation (gotong royong), deliberation (musyawarah), and respect for differences—serve as an effective foundation for shaping students' tolerant character. The study concludes that the better the implementation of multicultural education based on local wisdom, the higher the students' tolerance attitudes. However, synergy between schools, teachers, parents, and the community, as well as the strengthening of systematic pedagogical strategies, is still needed to optimize the outcomes.